RETN Gene Single Nucleotide Polymorphism Profile on Triglyceride-Glucose Index as Insulin Resistance Proxy Among Cohort Population of Non-Communicable Diseases in Bogor - Frans Dany; Uly Alfi Nikmah; Ratih Rinendyaputri; Fitrah Ernawati; Dewi Kristanti; Fifi Retiaty (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2022)
Genetic factors such as single nucleotide polymorphisms (SNPs) are thought to contribute to the increasing incidence of diabetes mellitus (DM) through insulin resistance. SNPs in the RETN (resistin) gene encoding the resistin protein have been reported to play a role in causing abnormalities in blood glucose and lipid metabolism. Still, studies related to this have rarely been explored in cohort population models. This study aimed to evaluate the relationship of resistin gene SNPs to the trend of the triglyceride-glucose index (TyG) as a proxy for insulin resistance. The data were obtained from the results of the biomedical laboratory examination among participants of a cohort study in the Kebon Kalapa subdistrict, Bogor, every odd year period between 2015-2021 and from RETN genotyping (rs3745367). The generalized linear model (GLM) repeated measurement technique was used with the TyG index value as the dependent variable. The results of the GLM analysis showed that although there was a significant difference in the trend of the TyG index between the observation periods [F(2,87, 1671,1)=41,10, p-value <0.001], that’s not the case for RETN gene SNP [F(5,73, 1671,1) = 1.09, p-value = 0.367]. However, the multivariate test results suggested the association of these SNPs with age and DM status [F(4, 583)=2.48, p-value = 0.043]. In conclusion, RETN gene SNPs may require interaction with other factors or genes to induce insulin resistance or act by indirect glucose–fatty acid metabolic cycle mechanisms.